Pemanfaatan Ubi Jalar Putih, Ubi Jalar Kuning, DanSingkong Sebagai Media Alternatif Potato DextroseAgar (PDA) Untuk Pertumbuhan Aspergillus niger - ISMAWATI, NURY, Triastuti Rahayu, S.Si, M.Si (2016)
The commontly medium used for fungus growth is PDA (Potato Dextrose Agar). The purpose of this research is to know the growth Aspergillus niger on alternative medium, that are White - fleshed sweet potato, Yellow - fleshed sweet potato, and Cassava. The method used in this study is experimental research using completely randomized design (CRD) with one factor that is kinds of medium PDA (M0), medium white - fleshed sweet potato (M1), medium yellow - fleshed sweet potato (M2), and medium cassava (M3) with using the fungus Aspergillus niger. The inoculation of Aspergillus niger use agar block method which incubated for 3 days with temperature 280C. The parameter of this research are colony diameter, sporulation, and the color micellium of Aspergillus niger. Data were analyzed with quantitative and qualitative methods. The result of this research showed the growth of Aspergillus niger after incubation during 72 hours, the diameter medium of PDA is 35,5 mm, medium White - fleshed sweet potatois 39 mm, medium Yellow - fleshed sweet potatois 33 mm and medium of Cassava is 37,5 mm with dense of sporulation and the best color micellium is media of PDA. So can be conclude that medium of White - fleshed sweet potato, Yellow - fleshed sweet potato, and Cassavacan used for subtitution of PDA medium for fungus growth.